Evaluating Mathematical Representation Competence Among Primary Students: Insights from the Post-Pandemic Learning Recovery - Yeni Yuniarti; Yunus Abidin; Naila Kurnia Restu (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The study aims to investigate not only the fundamental mathematical knowledge of primary school students but also their mathematical representation skills, as these are essential for applying mathematical concepts in everyday life. Methodology: A descriptive research design was employed without any treatment. The instrument included a test measuring representation skills through three indicators: forming equations or models from given representations, drawing diagrams to clarify and solve problems, and composing stories based on given representations. Secondary data were gathered through field notes and analysed using descriptive statistics, followed by triangulation with observation results. Main Findings: The findings reveal that students’ mathematical representation skills remain underdeveloped. The lowest performance was observed in the indicator involving drawing diagrams to support problem-solving. These results suggest a mismatch between students' learning needs and current instructional strategies, underscoring the need to implement differentiated and inclusive approaches to better support diverse learners. Novelty/Originality of this study: The study introduces a validated diagnostic test administered prior to the main assessment, ensuring the reliability and validity of the research results. This approach minimises bias and provides a more accurate portrayal of students' actual representation abilities, offering new insights into differentiated learning in mathematics education.